Isolamento e caracterização de vB_XciM_LucasX, um novo bacteriófago lítico de Xanthomonas citri e Xanthomonas fuscans - Monteiro, Vinícius Marquioni (2022)
Citrus canker, which is caused by the bacteria Xanthomonas citri and Xanthomonas fuscans, is one of the main diseases that affect the citrus industry in Brazil. Disease control methods are available, but new methods are necessary. A possible way to combat citrus canker is biocontrol using bacteriophages, also called phages, which are viruses that infect bacteria and which have been proposed as an alternative to the use of other antibacterial methods for agriculture and human health. The objectives of this doctoral project were the isolation, sequencing and characterization of one or more phages capable of infecting Xanthomonas citri, as well as to assess their potential for biocontrol of citrus canker. From a soil sample collected in a citrus grove affected by citrus canker, we could isolate a phage capable of infecting X. citri, strain 306, also known as Xac 306. The phage has a 305,651-bp, dsDNA genome, with a GC content of 54.92% and three hundred ninety-four ORFs, for one hundred eighty-one of which it was possible to assign functions while two hundred and thirteen remained as hypothetical. Phylogenetic and microscopy analysis allowed the classification of the phage in the Myoviridae family and it was named vB_XciM_LucasX. LucasX infected twenty-one of the twenty-three strains of X. citri and X. fuscans against which it was tested. A pangenomic analysis with the strains whose genome is available indicated that a 40-kbp region is present in all susceptible strains, but absent in the resistant strain, and which must contain genes essential for phage infection. LucasX can be propagated in NB medium but not in LB medium, probably because it is not tolerant to NaCl. LucasX is stable up to 45oC, has a latent period of 90 min and a burst size of 40 PFU/infected cell, its optimal pH is 7 and it can be inactivated with 40% ethanol or by being exposed to UV light from a germicidal lamp. The phage yield in liquid medium was studied in three strains of Xanthomonas sp. and it was one order of magnitude higher in one of them relative to the strain used for isolation. Finally, an experiment with citrus trees kept in a greenhouse showed that LucasX is able to reduce the number of lesions caused by Xac 306 by up to 89%%, a reduction similar to that of a commercial bactericide used as a control, thus indicating its potential as a biocontrol agent for citrus canker.